PENGARUH KOMBINASI PIJAT WOOLWICH DAN DO’A PILIHAN MENGGUNAKAN ROLL ON SAUM OIL TERHADAP EFIKASI DIRI IBU MENYUSUI: Pijat Wolwich, Efikasi Diri, Primigravida - Dewi Andariya Ningsih; Liana Devi Oktavia (JOMIS (Journal of Midwifery Science), 2025)
Breast milk is the best nutrition for babies, Obstacles during the breastfeeding process often become obstacles and lack of confidence in mothers in providing maximum breast milk. One of the complementary therapies that is easy for breastfeeding mothers to do is Wowich Massage. So that breastfeeding mothers can apply massage independently by listening to the prayer of choice and after the massage is finished. Mothers can apply Roll On Saum Oil on the mother's back as an additional sense of relaxation. The study's objectives were to ascertain the outcomes of the organoleptic test for creating saum oil as a massage oil for nursing moms and the impact on primiparous mothers' self-efficacy by combining roll-on saum oil with woolwich massage and prayer of choice. One group was employed for the pre- and post-tests in the research investigation. Shapiro normal test for organoleptic testing. A different test that makes use of the vital walis. Thirty persons participated in the organoleptic test. Using the Shapiro test to assess normalcy, the effect of combining a Wolwich massage with Roll-On Saum Oil and Prayer of Choice on nursing moms' self-efficacy is examined. According to the Sig value, the study's findings demonstrated a substantial difference in self-efficacy before and after the intervention. 0.000 (<0.050). In the meantime, the N positive ranks number of 38 indicates the increase that all respondents experienced. One of the best complementary therapies for promoting breastfeeding continuation is wolwich massage combined with certain prayers.